Pengaruh Perbedaan Budaya Komunikasi terhadap Kesalahpahaman Sosial pada Mahasiswa Perantau - Mitha Rafina; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the effect of cultural differences in communication on social misunderstandings among migrant students. The study uses a single-subject experimental method or Single Subject Research (SSR), with the subject being a 22-year-old student with the initials KL from Medan, who is studying at a university in Bukittinggi. Data were collected through observation, counseling interviews, and analysis of the counselee’s behavior. The intervention was carried out using the Transactional Analysis approach with techniques of providing information, providing examples, and giving advice. The results show that cultural differences in communication, particularly in the use of the word “kau,” caused social misunderstandings between the counselee and peers in the Minangkabau environment. This condition led to strained interpersonal relationships, feelings of guilt, social anxiety, and difficulty adjusting to the new environment. Through culturally informed counseling, the counselee began to understand the differences in communication norms, recognized the importance of adjusting word choice, and was guided to use the Adult ego state in communication. The findings indicate that understanding cultural differences in communication is essential in helping migrant students build better social relationships and reduce intercultural misunderstandings.